Experimental and numerical modeling of CO2 leakage in the vadose zone. Issue 6 (24th August 2015) - Gasparini, Andrea; Credoz, Anthony; Grandia, Fidel; Garcia, David Angel; Bruno, Jordi
Abstract: This study presents the experimental and modeling results of CO2 injection and transport in the vadose zone performed in PISCO2 facilities at the ES.CO2 center in Ponferrada (North Spain). During 46 days of experiments, 62.10 kg of CO2 were injected through 16 micro‐injectors in a 35 m 3 experimental unit filled with sandy material. Monitoring and mapping of surface CO2 flux were performed periodically to assess the evolution of CO2 migration through the soil and to the atmosphere. Numerical simulations were run using TOUGH2 code with EOS7CA research module considering two phases (gas and liquid) and three components (H2 O, CO2, air). Two layers (sand, gravel) and atmosphere boundary were implemented taking into account heterogeneous soils, homogeneous soil, rainfall, temperature, and liquid saturation to allow a better understanding of CO2 behavior in the vadose zone. This combined experimental and modeling approach shows that CO2 leakage in the vadose zone quickly comes out through preferential migration pathways and spots with the ranges of fluxes in the ground/surface interface from 2.5 to 600 g·m −2 ·day −1 . This gas channeling is mainly related to soil compaction and climatic perturbation. This has significant implications for design‐adapted detection and monitoring strategies of early leakage in commercial CO2 storage. © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd